Case Report: Coexistent Wolff-Parkinson-White Syndrome and Brugada Phenocopy in a Patient With Pneumonia and Myocarditis - Wang, Li; Zhao, Yana; Ma, Lan (Frontiers in Cardiovascular Medicine, 2021)
Background: In recent years, Wolff-Parkinson-White (WPW) syndrome and Brugada electrocardiogram (ECG) patterns have been reported as coexistent in the same patient. In most cases, the two waveforms appeared separately. Here, we described combinations of different waveforms on one ECG, such as the Brugada pattern with delta waves and the Brugada pattern with paroxysmal supraventricular tachycardia (PSVT). Importantly, we recorded an alternate conversion of these combined ECG waveforms, which has not previously been reported in the literature. At the same time, we confirmed that the change in the waveform was related to fever by analyzing Holter data. Case: A 48-year-old male was admitted to our hospital due to palpitations and fever. The patient had a history of a cold 3 days ago. Laboratory examinations showed an elevated neutrophil percentage (85%) and troponin I level (0.86 ng/ml). A chest computed tomography (CT) scan showed inflammation in the right lung. The diagnosis of pneumonia and myocarditis was made. ECG indicated WPW syndrome and the Brugada pattern. We recorded the dynamic changes in this combination of delta waves and Brugada waves with a Holter monitor, and we found the changes would happen when the patient's body temperature rose. The doctors thought that the patient's pulmonary infection led to fever, which caused the changes in waveform. After treatment with antibacterial therapy and supportive care, his body temperature returned to normal. The various laboratory indicators also gradually returned to normal. The doctor recommended that the patient undergo further pre-excitation bypass radiofrequency ablation treatment, but the patient refused and was discharged. Conclusion: Delta waves and Brugada ECG patterns could appear on one ECG at the same time. There were dynamic changes of QRS complex, relating to fever.